Smart care spaces: pervasive sensing technologies for at–home care. (23rd September 2014) - Thomas, A.M.; Moore, P.; Evans, C.; Shah, H.; Sharma, M.; Mount, S.; Xhafa, F.; Pham, H.V.; Barolli, L.; Patel, A.; Wilcox, A.J.; Chapman, C.; et al.
Society is experiencing an ageing demographic, coupled with increasingly prevalent Alzheimer and Dementia conditions, expected to cause explosive increases in healthcare costs. There is a need to develop pervasive technologies that allow monitoring of patients at home, where medically permissible, to reduce pressures on formal healthcare spaces. Those 'smart care spaces' require use of sensors and intelligent computer systems to support the needs of the cared–for, carers and medical personnel. In so doing they can ensure quality–of–life through comfort and adequate medical–monitoring, as well as providing significant data for ongoing medical evaluation and diagnosis. This requires two main elements of sensing: sensors to monitor the care environment and patient–mounted sensors to monitor physiological parameters. Therefore, this paper considers technological options available for such monitoring and provides examples of their use. It will be concluded that cost-effective solutions are available for development of smart care space monitoring.